2018
DOI: 10.1101/323980
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The genetic architecture of target-site resistance to pyrethroid insecticides in the African malaria vectorsAnopheles gambiaeandAnopheles coluzzii

Abstract: 14Resistance to pyrethroid insecticides is a major concern for malaria vector con-15 trol, because these are the compounds used in almost all insecticide-treated bed-nets 16 (ITNs), and are also widely used for indoor residual spraying (IRS). Pyrethroids target 17 the voltage-gated sodium channel (VGSC), an essential component of the mosquito 18 nervous system, but substitutions in the amino acid sequence can disrupt the activity 19 of these insecticides, inducing a resistance phenotype. Here we use Illu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 36 publications
7
66
0
Order By: Relevance
“…Instead, 296G and 296S haplotypes have accumulated additional non-synonymous mutations ( Figure 3A), some of which (codon 345) are putatively compensatory. As mentioned above, a similar altered selective regime has also been observed in Vgsc haplotypes with kdr mutations (Clarkson et al 2018).…”
Section: Persistence Of Rdl Mutations After Dieldrin Withdrawalsupporting
confidence: 69%
See 3 more Smart Citations
“…Instead, 296G and 296S haplotypes have accumulated additional non-synonymous mutations ( Figure 3A), some of which (codon 345) are putatively compensatory. As mentioned above, a similar altered selective regime has also been observed in Vgsc haplotypes with kdr mutations (Clarkson et al 2018).…”
Section: Persistence Of Rdl Mutations After Dieldrin Withdrawalsupporting
confidence: 69%
“…Instead, 296G and 296S haplotypes have accumulated additional non-synonymous mutations ( Figure 3A), some of which (codon 345) are putatively compensatory. As mentioned above, a similar altered selective regime has also been observed in Vgsc haplotypes with kdr mutations (Clarkson et al 2018). Interestingly, a study of Brazilian Aedes aegypti found that Vgsc kdr mutations did not decrease in frequency after a decade without public pyrethroid spraying campaigns (Macoris et al 2018).…”
supporting
confidence: 69%
See 2 more Smart Citations
“…The next-generation sequencing (NGS) technology has revolutionized almost all fields of biology by reducing the cost and time of DNA sequencing by orders of magnitude. The recent Anopheles gambiae 1000 Genomes project, Ag1000G, has uncovered a number of previously unknown nonsynonymous mutations in the VGSC gene in A. gambiae and A. coluzzii (Clarkson et al, 2018), some of which have been suspected to cause resistance directly or indirectly. The study also showed that even neutral variations within or flanking the VGSC locus represent valuable information to infer the origin and evolution of resistance.…”
Section: Introductionmentioning
confidence: 99%